Microtubule Binding and Trapping at the Tip of Neurites Regulate Tau Motion in Living Neurons - Carina Weissmann; H.-J. Reyher; Anne Gauthier; Heinz‐Jürgen Steinhoff; Wolfgang Junge; Roland Brandt (2009)
During the development of neurons, the microtubule-associated tau proteins show a graded proximo-distal distribution in axons. In tauopathies such as Alzheimer's disease, tau accumulates in the somatodendritic compartment. To scrutinize the determinants of tau's distribution and motion, we constructed photoactivatable green fluorescent protein (GFP)-tagged tau fusion proteins and recorded their distribution after focal activation in living cells. Simulation showed that the motion of tau was compatible with diffusion/reaction as opposed to active transport/reaction. Effective diffusion constants of 0.7-0.8 microm(2)/second were calculated in neurites of PC12 cells and primary cortical neurons. Furthermore, tau's amino terminal projection domain mediated binding and enrichment of tau at distal neurites indicating that the tip of a neurite acts as an adsorber trapping tau protein. Treatment with taxol, incorporation of disease-related tau modifications, experimentally induced hyperphosphorylation and addition of preaggregated amyloid beta peptides (Abeta) increased the effective diffusion constant compatible with a decreased binding to microtubules. Distal enrichment was present after taxol treatment but was suppressed at disease-relevant conditions. The data suggest that (i) dynamic binding of tau to microtubules and diffusion along microtubules and (ii) trapping at the tip of a neurite both contribute to its distribution during development and disease.